Ability of plant species to colonise human‐disturbed habitats: Role of phylogeny and functional traits. Issue 1 (30th September 2020) - Mudrák, Ondřej; Řehounková, Klára; Vítovcová, Kamila; Tichý, Lubomír; Prach, Karel
Abstract: Question: Which species are successful colonisers of disturbed sites; species adapted to seed dispersal, resistance to abiotic stress, or competition ability? Are successful adaptations for colonisation shared by phylogenetically related species? Location: Czech Republic, Central Europe. Methods: We used two indices of plant species' colonisation ability (developed from an extensive dataset of dated successional series for 1, 531 plant species of the Czech Republic): index of colonisation potential (ICP), which is corrected for mass effect (species' frequency in the landscape acquired from Czech National Phytosociological Database, accounting for more common colonisation events of frequent species), and index of colonisation success (ICS), which is solely based on actual species frequencies in disturbed habitats. We also used preferences for successional age (median of age of sites that species had colonised). We correlated these indices with plant functional traits for three functional groups (woody species, non‐woody perennial polycarpic, and non‐woody monocarpic species) either considering the phylogenetic history of a species or not. Results: Woody species were the best colonisers and had the highest preferences for late‐successional stages. Non‐woody monocarpic species had a higher ICP than polycarpic species while their ICS were comparable. The best predictor of colonisation ability of both monocarpic and polycarpic non‐woody species was canopy height, indicating importance of competition. Other successful colonisers were species with seed traits promoting dispersal (low seed mass or low seed terminal velocity). We did not find traits suitable for adverse biotic conditions (high specific leaf area, SLA), low canopy height) to be important. Successional age preference of species was indicated mainly by seed traits (seed mass, seed longevity), which highly corresponded with species' phylogenetic history. Conclusions: Colonisation of disturbed sites is limited by seed dispersal and competitive interactions rather than an adverse abiotic environment. Abstract : Woody species were the most successful colonisers of Central European disturbed sites. Non‐woody species were less common and their colonisation was well predicted by canopy height and by seed traits. These indicate that colonisation of disturbed sites is limited by seed dispersal and competitive interactions rather than an adverse abiotic environment.